(untitled) - Weaver, Connie M. (Boca Raton, FL., 2003)
A popular book in its first edition, The Food Chemistry Laboratory: A Manual for Experimental Foods, Dietetics, and Food Scientists, Second Edition continues to provide students with practical knowledge of the fundamentals of designing, executing, and reporting the results of a research project. Presenting experiments that can be completed, in many cases, without requiring extensive student laboratory facilities, the authors include new exercises in the areas of physical properties, lipids, proteins, and gelatin. Also new in this edition are a brief introduction to each laboratory exercise and a listing of materials needed, approximate time needed for completion, and possible complications and/or pitfalls.
Hóa học thực phẩm,Hóa học thực phẩm
Keywords: Food,Food; Analysis,Composition